EL DIBUJO TÉCNICO MANUAL Y SU VIGENCIA EN EL ACTUAL CONTEXTO TECNOLÓGICO - GIOVANY SUÁREZ PINILLA (Revista Ingeniería, Matemáticas y Ciencias de la Información)
From ancient times, drawing has been used to express both the artistic and scientific ideas created in human brain.Although drafting -otherwise known as technical drawing made by hand- is a traditional subject taught at universities forengineering and architectural programs, current trends tend to replace it for computer assisted drawing software. Yet newtechnologies, in particular ICTs (information and communication technology) support with a large number of advantagesthe learning process, freehand drawing also provide students with very powerful skills that will be of their greatest benefitat school and work. Through the following paragraphs, the author presents a brief review about the relationship betweendrawing and science as well as the significant role that freehand drawing plays in the current times.